2018
DOI: 10.1002/tl.20320
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Excellent Teachers: International, HBCU, and Health Professions Perspectives

Abstract: 9Four TBC studies investigating faculty and student perceptions of the qualities of excellent teachers yielded consistent results, although student responses revealed a greater range of qualities. Students included more items from the caring and supportive subscale whereas faculty tended to focus more on items from the professional competency subscale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Previous research using the TBC sought to identify the top behaviors related to effective teaching, and several studies show consistent results. Findings from Ford’s (2016) pharmacy-focused study, Schaeffer et al’s (2003) community college study, Buskist et al’s (2002) research-intensive university study, and this study show that faculty agree on five of the top 10 behaviors: knowledgeable, enthusiastic, approachable/personable, creative/interesting, and promotes critical thinking (Groccia et al, 2018). In addition, and specific to health professions, faculty in Ford’s (2016) study and this study identified eight of the same behaviors in their top 10.…”
Section: Discussionmentioning
confidence: 56%
“…Previous research using the TBC sought to identify the top behaviors related to effective teaching, and several studies show consistent results. Findings from Ford’s (2016) pharmacy-focused study, Schaeffer et al’s (2003) community college study, Buskist et al’s (2002) research-intensive university study, and this study show that faculty agree on five of the top 10 behaviors: knowledgeable, enthusiastic, approachable/personable, creative/interesting, and promotes critical thinking (Groccia et al, 2018). In addition, and specific to health professions, faculty in Ford’s (2016) study and this study identified eight of the same behaviors in their top 10.…”
Section: Discussionmentioning
confidence: 56%
“…Second, it became increasingly evident throughout this project that there is a separate research literature on caring teachers and how it is their caring orientation makes them so effective (e.g., Groccia et al, 2018;Meyers, 2009;Walker & Gleaves, 2016). This literature has developed in parallel with the research literature on mattering with little attempt at integration, and, to our knowledge, mattering and caring have not been described as inter-connected until now.…”
Section: Discussionmentioning
confidence: 99%